On mechanical, thermal and morphological investigations of almond skin powder-reinforced polylactic acid feedstock filament. (February 2022) - Singh, Rupinder; Kumar, Ranvijay; Pawanpreet,; Singh, Mohit; Singh, Jatenderpal
The almond skin powder is one of the biodegradable and biocompatible food wastes that can be used as reinforcement in polylactic acid (PLA) for preparation of biomedical scaffolds/implants (for high mechanical performance) by fused filament fabrication. The present study deals with the melt processing of almond skin powder as reinforcement from 0 wt% to 5 wt% in the PLA matrix by twin-screw extrusion process. The results of the study suggested that reinforcing the almond skin powder as 2.5 wt% in the PLA matrix mechanically strengthens the feedstock filaments but the increase in the proportion up to 5 wt% reduces the mechanical strength to a significant level. A similar trend has been observed in differential scanning calorimeter observations for thermal stability analysis. As regard to the rheological property is concerned, the melt flow index shows a significant reduction with reinforcement of almond skin powder in PLA. The results are also supported by photomicrographic analysis (for surface properties) and Taguchi-based optimization of twin-screw extrusion process parameters (for multifactor optimization).